Influencing Factors of Thermogenic Adipose Tissue Activity - Zhang, Guoqing; Sun, Qinghua; Liu, Cuiqing (Frontiers in Physiology, 2016)
Obesity is an escalating public health challenge and contributes tremendously to the disease burden globally. New therapeutic strategies are required to alleviate the health impact of obesity-related metabolic dysfunction. Brown adipose tissue is specialized for dissipating chemical energy for thermogenesis as a defense against cold environment. Intriguingly, the brown-fat like adipocytes that dispersed throughout white adipose tissue in rodents and humans, called “brite” or “beige” adipocytes, share similar thermogenic characteristics to brown adipocytes. Recently, researchers have focused on cognition of these thermogenic adipose tissues. Some factors have been identified to regulate the development and function of thermogenic adipose tissues. Cold exposure, pharmacological conditions and lifestyle can enhance non-shivering thermogenesis and metabolism via some mechanisms. However, environmental pollutants, such as ambient fine particulates and ozone, may impair the function of these thermogenic adipose tissues and thereby induce metabolic dysfunction. In this review, the origin, function and influencing factors of thermogenic adipose tissues were summarized and it will provide insights into identifying new therapeutic strategies for the treatment of obesity and obesity-related diseases.